Solvent Engineering Approach Toward Optimized Phase and Morphology of CsPbBr3 Films for Efficient and Stable Planar Perovskite Solar Cells and Photodetectors. Issue 11 (18th September 2022) - Xu, Kaiyuan; Zhou, Long; Chen, Xi; Zhang, Siyu; Guo, Xing; Shou, Chunhui; Lin, Zhenhua; Zhang, Jincheng; Chang, Jingjing; Hao, Yue
Abstract : All‐inorganic perovskite CsPbBr3 has drawn a lot of interest as an active layer applied in photovoltaics due to its outstanding stability in ambient air. However, the procedure of preparing high‐quality CsPbBr3 films still remains a serious challenge because of the tedious process and toxic solvent. Herein, a solvent engineering method that involves green solvent with mixed H2 O/C2 H5 OH to dissolve CsBr is presented to produce all‐inorganic perovskite CsPbBr3 films. CsPbBr3 perovskite solar cells (PSCs) are fabricated based on planar n‐i‐p structure. Compared with CsBr H2 O solution, the CsPbBr3 films with optimized mixed solvent method exhibit larger grain size and improved crystallinity. As a result, the carbon‐electrode PSCs based on the mixed solvent method exhibit an increased efficiency of 9.70%. The best‐performing device retains 96.95% of the initial power conversion efficiency (PCE) after storing 1000 h under ambient air and 86.46% of the initial PCE after continuous illumination for 100 min. Moreover, the photodetector based on the same structure as the CsPbBr3 device shows high responsivity and high detectivity. The result not only provides an easy and straightforward method to prepare the uniform and pinhole‐free CsPbBr3 films, but also reduces the toxicity of the CsBr solution used to make the CsPbBr3 PSCs. Abstract : A solvent‐engineering strategy is used to create high‐quality CsPbBr3 films with increased grain size and crystallinity and reduced carrier interfacial recombination. Finally, the multi‐function champion device has a satisfactory power conversion efficiency of 9.70% in the solar cell and a high detectivity of 2.5 × 10 14 Jones in the photodetector.